MMHT Updates, LHC jets and α S - Thorne, R; Harland-Lang, L; Martin, A (Sissa Medialab, 2018)
We summarise the effects of including jet data from the LHC in the MMHT PDF extraction. We also present the latest results on the preferred value of the strong coupling αS(MZ2) in a number of fit variations. The best current value with all new data is αS(MZ2) = 0.1176.